Mating type gene for isolates of Trichophyton mentagrophytes from guinea pigs. Issue 8 (August 2014) - Hiruma, Junichiro; Kano, Rui; Kimura, Utako; Takamori, Kenji; Suga, Yasushi; Hiruma, Masataro; Hasegawa, Atsuhiko; Tsuboi, Ryoji
Abstract Trichophyton mentagrophytes were isolated from 19 of 20 guinea pigs in a children's corner of a zoo. The nucleotide sequence identity of the internal transcribed spacer region among 19 guinea pig isolates was 99%, including the reference strain of animal type 3 of T. mentagrophytes. The genomic DNA of all isolates were investigated for the mating (MAT) gene by specific polymerase chain reaction. The alpha‐box gene was detected in all 19 isolates, while the high‐mobility‐group (HMG) gene was detected in only one of 19 isolates. Therefore, the guinea pig population harbored at least 2 MAT types of Arthroderma vanbreuseghemii. The T. mentagrophytes that was prevalent in this population may constitute a constant source of infection for persons coming into contact with guinea pigs.